PENGARUH MOTIVASI INTRINSIK DAN KUALITAS HUBUNGAN DENGAN ORANG TUA TERHADAP SELF-REGULATION SISWA FULL DAY SCHOOL - Muqoddam, Faqihul (CV. Jendela Gagasan, 2024)
Pancasila serves as the philosophical foundation of Indonesia’s national education system, reflecting the values of the nation in shaping character and identity through education. This study employed library research, and analyzes various sources of literature to understand Pancasila’s role in developing and maintaining the national education system. The findings indicate that the values of Pancasila’s are systematically implemented into educational polices, curricula, and teaching methods, that support intellectual and moral development. These efforts emphasizes the importance of Pancasila in uniting the diverse values and reinforcing its position as a moral compass and educational foundation in Indonesia.